2017
DOI: 10.1038/nsmb.3411
|View full text |Cite
|
Sign up to set email alerts
|

5-Formylcytosine does not change the global structure of DNA

Abstract: The mechanism by which 5-formylcytosine (fC) is recognised by enzymes involved in epigenetic modification and reading of DNA is not known, and recently an unusual DNA structure (F-DNA) was proposed as the basis for enzyme recognition of clusters of fC. We used NMR and X-ray crystallography to compare several modified DNA duplexes with the unmodified analogues and show that in the crystal state they all belong to the A-family, but in solution they are all members of the B-family. Contrary to the previous study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 58 publications
(68 reference statements)
4
65
0
Order By: Relevance
“…The unmodified duplex (blue, PDB 5MVK) closely resembles its f C‐containing analog when crystallized under moderate salt conditions (magenta, PDB 5MVU). The same f C‐duplex, when crystallized in a buffer containing very high salt – 1.8 M lithium sulfate (green, PDB 4QKK), is also conformationally similar to the control, except at the unmodified ends, which are distorted due to crystal packing interactions . b) Overlays showing the base‐stacking between base pairs X4 · G′9 and G5 · X′8 of the structures featured in (a) showing that the base‐stacking geometry of f CpG steps is not unusual.…”
Section: Dna Containing Epigenetic Modifications: What Features Do Bimentioning
confidence: 71%
See 2 more Smart Citations
“…The unmodified duplex (blue, PDB 5MVK) closely resembles its f C‐containing analog when crystallized under moderate salt conditions (magenta, PDB 5MVU). The same f C‐duplex, when crystallized in a buffer containing very high salt – 1.8 M lithium sulfate (green, PDB 4QKK), is also conformationally similar to the control, except at the unmodified ends, which are distorted due to crystal packing interactions . b) Overlays showing the base‐stacking between base pairs X4 · G′9 and G5 · X′8 of the structures featured in (a) showing that the base‐stacking geometry of f CpG steps is not unusual.…”
Section: Dna Containing Epigenetic Modifications: What Features Do Bimentioning
confidence: 71%
“…In contrast to the rotational dimorphism exhibited by the hydroxymethyl group of hm C, the formyl group of f C appears to be fixed in a single conformation in the plane of the cytosine ring facing toward the exocyclic N4‐amine, likely forming an intramolecular hydrogen bond (Figures b and 5a) . NMR‐based solution studies of f C‐modified DNA duplexes, and NMR and crystallographic studies of the free nucleoside have confirmed that this is the preferred conformation .…”
Section: Dna Containing Epigenetic Modifications: What Features Do Bimentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of densely fC‐modified DNA duplexes, conflicting results have been reported. In one study, significant fC‐induced changes of the duplex conformation were observed, whereas a second study reported crystal structures of fC‐modified duplexes with the same sequence (crystallized in a different space group) that exhibited only miminal changes in conformation compared to the corresponding unmodified duplexes (additional NMR studies supported the latter finding) . If dense modification of DNA with other oxidized mC derivatives can significantly affect DNA duplex conformations remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Biological effects of higher methylation levels at promoters are mediated by lowering the transcription of genes either by blocking the binding of transcription factors or by recruiting unique methyl-recognizing proteins that lower gene expression. Epigenetic modifications such as DNAmethylation play akey role in this endeavour.D NA methylation can be controlled by genetic means.Y et there are few chemical tools available for the spatial and temporal modulation of this modification.…”
mentioning
confidence: 99%